A Global Review of Government Policy on Reverse Logistic based on Bibliometric Analysis - Heliantina, Farah; Maksum , Irfan Ridwan; Prasetyo , Umanto Eko (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
Industrial progress and population growth are increasing the demand for food from rural to urban, requiring an efficient logistics system. Reverse logistics manages food waste by recycling unsold products, improving transportation efficiency and product quality, and supporting sustainability. However, policy fragmentation, a pressing issue, hinders effective implementation. Therefore, policy integration, a crucial step, is essential to achieve sustainability in reverse logistics systems, ensuring optimal coordination and use of resources. Limited studies offer a thorough understanding of government policy integration in reverse logistics, which bibliometric analysis can help address by providing a comprehensive overview of existing research